Palliative care in stroke: a nutritional look - Loss, Igor Oliveira (2021)
This is a theoretical-reflective study carried out in 2020. It was based on the analysis of books, documents and scientific articles obtained in databases, with the aim of elaborating reflections on nutritional approaches in the palliative care of patients affected by strokes. The guiding question was: What are the contributions of the nutritional approach for patients affected by strokes in palliative care? 15 references were considered, most of them international. The reflective axes were: Palliative care in stroke; Nutritional approaches in palliative care; and Nutritional approaches in palliative care in stroke. In addition to specific palliative guidelines and professional training, combating prognostic inaccuracies after the event is essential. Although nutritional interventions are of varying importance in the palliative approach of this patient, they must always respect the autonomy of the patient and their family. Stroke is a great cause of death and functional disability worldwide. The provision of palliative care as part of continuous care and integrated into the Unified Health System has recently been standardized and the issue of nutrition in a palliative situation needs a greater national approach.